Dramatic weight loss with rufinamide. Issue 1 (10th July 2012) - Mourand, Isabelle; Crespel, Arielle; Gelisse, Philippe
Summary Rufinamide (RUF) is a novel antiepileptic drug considered as second‐line therapy in the treatment of Lennox‐Gastaut syndrome. Treatment‐emergent adverse events (AEs) have consisted mainly of drowsiness, irritability, vomiting, and loss of appetite. RUF is considered as a "weight‐neutral" drug. We found clinically significant weight loss in 7 of 15 consecutive adult patients (47%; 3 male, 4 female, aged 18–31 years) treated with RUF as add‐on therapy (800–2, 400 mg/day: 23.5–57.1 mg/kg/day). The body mass index (BMI) decreased by 7.3–18.7%. Two patients were obese class I before RUF. Five patients (71%) were underweight before RUF (mild in one case, moderate in two cases, and severe in two cases). Four of these patients stopped RUF because of this adverse effect. RUF was recommenced in two patients using a lower and slower dosing strategy; one patient showed improvement in seizure control and no weight loss but RUF was re‐stopped in the second patient because of continued weight loss. Despite of weight loss, RUF was continued in two other patients because it reduced seizure activity. We primarily related weight loss to reduced food intake, that is, loss of appetite and nausea, although in two patients no obvious loss of appetite was reported. RUF can cause clinically significant weight loss in adult patients, even at low dose. This AE can affect patients who are already underweight. There is a possibility that lower starting doses and slower escalation might minimize weight loss, but further information is required to determine whether this is the case.